Efforts to prevent Covid-19 through education with booklet in Watuburik Village - Saelan Saelan; Galih Setia Adi; Sahuri Teguh Kurniawan (Community Empowerment, 2022)
Cases of Covid-19 reached Indonesia in March 2020 and have continued to rise since then, albeit positive numbers are now on the fall. The team discovered Covid-19 patients in Watburik Hamlet, Wonorejo Village, based on survey data, necessitating independent preventative actions. During the Covid-19 pandemic, the community, such as posyandu cadres, RT heads, and community leaders, are required to stop the virus from spreading. One of the efforts is to live a healthy lifestyle, keep the house clean, and follow health routines. The booklet media education technique will be used to carry out the Covid-19 preventive education method, which includes counseling on hand washing with six stages, keeping at home, avoiding crowds and community meetings, and wearing masks while sick and in public areas (markets, worship places, etc.), the installation of billboards, and the supply of disinfectants and hand soap. The billboard installation is done in collaboration with members of the community and partners. The outcomes of this activity's evaluation were able to raise public knowledge about the importance of adopting health standards in order to prevent Covid-19.